PENGARUH KOMPETENSI DAN LINGKUNGAN KERJA TERHADAP KINERJA PERAWAT BAGIAN RAWAT INAP PADA RUMAH SAKIT UMUM DAERAH (RSUD) PETALA BUMI PEKANBARU - Albert Wibi Rahman; Marzolina -; Taufiqurrahman - (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The research conducted in hospitals Petala Bumi Pekanbaru. In order to determine the effect of competence and work environment simultaneously and partially on the performance of nurse in hospitals Petala Bumi Pekanbaru. Populations in this study are all part of inpatiend RSUD Petala Bumi nurse who total 35 people and the entire population by cencus method. Performed data analysis and quantitative descriptive analysis using multiple linear regression with SPSS version 20. From the test results simultaneously (f-test) showed that the independent variables studied competence and work environment simultaneously significant effect on the performance of nurse and partial test result (t-test) showed that the variable competence and work environment is partially significant effect on the performance of nurse. Based on the coefficient of determination (R2) that the variable competence and work environment has an influence on the performance of nurses while the rest influenced by other variables not examined in this research. Suggestion can author is given to RSUD Petala Bumi is Hospital should further improve the competence and more attention to the work environment so that employes have a good performance and patient become more satisfied. Keywords: competency, work environment, and performance of nurses